The Problem of Linguistic Specification of Ukrainian Surnames in in the Works of Anthroponymists in XX–XXI Centuries (Linguostylistic Studies, 2016)
The article clarifies the approaches of antroponimists concerning the history of formation and linguistic specificity of Ukrainian surnames. The author offers insights into the scholars’ achievements in exploring the problem of the term «surname» meaning, highlighting the key distinctive features of surnames as a type of anthroponyms, and defines the chronology of their appearance. It has been specified that the process of establishing the family names was gradual and covered the following main stages: the emergence of a person’s two-word naming on a certain territory; stabilization of the basic word-formative types of modern surnames; juridical regulation of surnames.  The author places importance on the lingual peculiarities of the inheritable anthroponyms formation, reveals the level of the extralinguistic factors’ influence on the appearance of surnames. Scientists’ conceptions and approaches concerning various characteristic aspects of this specific kind of anthroponyms  have been systematized in the article.Key words: surname, anthroponomy, anthroponym, onomastics. References